CONTRIBUTION OF FUZZY LOGIC IN THE CRITICALITY RISK ASSESSMENT - Dhiaf, Mohamed Mahjoub (Yugoslav Journal of Operations Research; Vol 28 No 1 (2018), 2017)
In order to determine the criticality of each risk, an assessment of the probability of occurrence (notion of frequency) and of the impact (notion of severity) will be estimated. The criticality is the product of the probability of its occurrence by the impact which the risk has on the project to see on the whole company. To arrive there, the practice of matrix or criticality grids inserting these two dimensions will be necessary. However, the criticality gridpresent insuciencies inherent in the subjective behavior of expert judgments and to the imprecise of the information engaged when in the assessment of the risk. Taking into account the problems involved inthe imperfection of the knowledge impliedon the Conventional Criticality Matrix (CCM), the objective of this work being to develop a Fuzzy Criticality Matrix (FCM) to the supportof these diculties. The proposed model aims at improving the (CCM) by describing them by a system of fuzzy inference. The proposed approach is applied to a test system which is the logistic division within the company SAROST S.A.